Compositional variability of food wastes and its effects on acetone-butanol-ethanol fermentation. (15th April 2020) - Poe, Nicholas E.; Yu, Dajun; Jin, Qing; Ponder, Monica A.; Stewart, Amanda C.; Ogejo, Jactone A.; Wang, Hengjian; Huang, Haibo
Highlights: Food wastes collected in the dining hall exhibited a high composition variability. The composition varibilty cause diverse butanol yields in Clostridial fermentation. High equivalent sugar and starch contents in food waste led to a high butanol yield. High fiber content in food waste led to a low butanol yield in fermentation. Butanol yield can be predicted by equivalent sugar and fiber contents in food waste. Abstract: Converting food waste into butanol via acetone, butanol, and ethanol (ABE) fermentation provides the potential to recover energy and value-added chemicals from food waste. However, the high variability of food waste compositions has hindered the consistency and predictability of butanol production, impeding the development of a robust industrial fermentation process. This study characterized the compositional variation of collected food wastes and determined correlations between food waste compositional attributes and butanol yields for a better prediction of food waste fermentation with Clostridium . The total sugar, starch, fiber, crude protein, fat and ash contents (on dry basis) in the food waste samples were in a range of 0.5–53.5%, 0–25.2%, 0.6–26.9%, 5.5–21.5%, 0.1–37.9%, and 1.4–13.7%, respectively. The high variability of food waste composition resulted in a wide range (3.5–11.5 g/L) of butanol concentrations with an average of 8.2 g/L. Pearson's correlation analysis revealed that the butanol concentrations were strongly and positively correlated with equivalent glucose and starch contents in food waste, strongly and negatively correlated with fiber content, and weakly correlated with total sugar, protein, fat, and ash contents. The regression models constructed based on equivalent glucose and fiber contents reasonably predicted the butanol concentration, with the R 2 of 0.80. Our study investigated the variability of food waste composition and, for the first time, unveiled relationships between food waste compositional attributes and fermentation yields, contributing to a greater understanding of food waste fermentation, which, in turn, assists in developing new strategies for increased consistency and predictability of food waste fermentation.